Flour Beetle Pheromones and Social Behavior - Yeoman, Hannah; Marshall, Jeremy (My University, 2017)
Being raised in a group or solitary can affect behavior of an animal. In this experiment, I am working with the red flour beetle, Tribolium castaneum. I am studying whether the way the beetles are raised affects their pheromone preference. I have been searching for similar studies and there are only a select few that are in a comparable format as my own. This is important, because it shows the connection between group living and solitary living and the preference for a certain scent. The question that I am asking for this study is if living in solitude or in groups can affect the insects behavior. My hypothesis elaborates on that question and reads: “my hypothesis is that living in groups will increase the preference for all pheromone types (other and self scent)”. However, the results I found are not consistent with my hypothesis. Instead, I found that there is a significant difference between the pheromone preference for the group-scent in the beetles raised as a group as opposed to the ones raised solitary. These results are key because it shows that the beetles who have been raised in a social environment not only recognize the scent of their peers, but prefer the scent of their own group.
Citation: Yeoman, H. (2017). Flour Beetle Pheromones and Social Behavior . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.